(untitled) (Journal of Plant Disease Sciences, 2022)
Numerous viruses have been discovered in plants, both domestic and wild, in recent years. The biodiversity of plant viruses has been studied using a variety of methods, including virus-specific DNA or RNA, followed by sequencing and bioinformatics analyses. All the analysis reveals more knowledge about plant viruses. Phylogenetic analyses are increasingly being used in epidemiology, to understand the pattern of DNA/RNA virus infection in soybean plants, while the Recombination detection program is also used to analyse nucleotide sequence data and to identify the evidence of genetic recombination between the viruses infecting soybean.This study have found evidence that recombination is an important impelling cause in the evolution and divergence ofmany plant viruses, including begomoviruses, potyviruses and other viruses.